Rappresentare e immaginare - Leardo Botti (Aisthesis, 2012)
This paper focuses on two expressions as distinct: “describing” and “painting” with words. Such a distinction is theorized by Leopardi in his Zibaldone and points to the way in which our imagination cooperates with perception in constituting our experience. In this framework I will further address the question of the “double object”.